2017
DOI: 10.3390/app7040351
|View full text |Cite
|
Sign up to set email alerts
|

Scan-Less Line Field Optical Coherence Tomography, with Automatic Image Segmentation, as a Measurement Tool for Automotive Coatings

Abstract: Abstract:The measurement of the thicknesses of layers is important for the quality assurance of industrial coating systems. Current measurement techniques only provide a limited amount of information. Here, we show that spectral domain Line Field (LF) Optical Coherence Tomography (OCT) is able to return to the user a cross sectional B-Scan image in a single shot with no mechanical moving parts. To reliably extract layer thicknesses from such images of automotive paint systems, we present an automatic graph sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…1(a) shows a schematic diagram of the LF-OCT system and pulse generation circuit module used in the study. The optical configuration of LF-OCT is similar to our previous work [31,32], but a low-cost infrared superluminescent diode (SLED) of 50 nm spectral bandwidth centred at 840 nm was used. Linefield illumination is achieved by a cylindrical lens.…”
Section: A System and Experiments Setupmentioning
confidence: 99%
“…1(a) shows a schematic diagram of the LF-OCT system and pulse generation circuit module used in the study. The optical configuration of LF-OCT is similar to our previous work [31,32], but a low-cost infrared superluminescent diode (SLED) of 50 nm spectral bandwidth centred at 840 nm was used. Linefield illumination is achieved by a cylindrical lens.…”
Section: A System and Experiments Setupmentioning
confidence: 99%
“…While online sensors are still scarce, the applicability of OCT for structural analysis for industrial purposes has been demonstrated in numerous cases. These include crystallization processes in polymers (Hierzenberger, 2014), liquid sorption in paper (Fabritius, 2007), thermal degradation of epoxy resin composites (Awaja et al, 2009), automotive coatings (Lawman et al, 2017a), nanocomposites (Schneider et al, 2016), polymer-fiber composites (Stifter et al, 2008), quality control of film coating (Koller et al, 2011;Nemeth et al, 2012;Markl et al, 2014a;Markl et al, 2015a;Markl et al, 2015b), and LCD-display production (Shirazi et al, 2016;Wijesinghe et al, 2017). An important functional extension of OCT, namely polarization-sensitive OCT (Boer et al, 2017), has been used, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is a high-resolution tomographic imaging technique that has multiple applications in the coating field [12,13], including measurement of flake statistics [14], dryness and surface texture [12], on top of layer thicknesses [15]. The technique is analogous to ultrasound, but instead measures the time delay of light reflections and scattering from within the sample, reletaive to to an engineered reference path (by coherence interferometry).…”
Section: Introductionmentioning
confidence: 99%